1993
DOI: 10.1159/000211146
|View full text |Cite
|
Sign up to set email alerts
|

Increased Superoxide Anion Production in Dermal Fibroblasts of Psoriatic Patients

Abstract: We studied the superoxide anion activity of psoriatic and normal dermal fibroblasts in culture. Superoxide anion production was measured by the technique of Pick and Mizel in fibroblasts cultured from biopsies of involved and uninvolved skin of patients with psoriasis and from skin biopsies of normal controls. Our results show that the liberation of superoxide anion was sig nificantly increased (p < 0.001) in fibroblasts obtained from involved areas of skin (5.58 nmol O2-/106cells/50 min)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Our previous studies showed an increased intracellular ROS production and an enhanced NADPH oxidase activity in fibroblasts obtained from lesional skin of psoriatic patients [6]. This data is in line with the findings of other authors who showed O 2 • − production, mitochondrial superoxide dismutase activity (Mn-SOD) and protein carbonylation level [7,8] to be significantly increased in fibroblasts obtained from involved and uninvolved skin of psoriatic patients in comparison to healthy skin fibroblasts.…”
Section: Introductionsupporting
confidence: 90%
“…Our previous studies showed an increased intracellular ROS production and an enhanced NADPH oxidase activity in fibroblasts obtained from lesional skin of psoriatic patients [6]. This data is in line with the findings of other authors who showed O 2 • − production, mitochondrial superoxide dismutase activity (Mn-SOD) and protein carbonylation level [7,8] to be significantly increased in fibroblasts obtained from involved and uninvolved skin of psoriatic patients in comparison to healthy skin fibroblasts.…”
Section: Introductionsupporting
confidence: 90%
“…The key role of dermal fibroblasts in regulating epidermal microenviroment, immune cell behaviour [ 26 , 27 ] and keratinocyte function has been already suggested [ 1 , 5 , 26 , 27 ]. Indeed, impaired fibroblasts can extensively produce superoxide and H 2 O 2 (modifying the redox balance of psoriatic derma), promote inflammatory mechanisms [ 28 ] and may contribute to the epidermal overgrowth by inducing keratinocyte proliferation [ 29 , 30 , 31 , 32 ]. Based on this background, fibroblast cultures derived from psoriatic lesions represent our selected experimental model.…”
Section: Discussionmentioning
confidence: 99%
“…Although hydrogen peroxide treatment resulted only in a transient and rather weak induction of HO-1 expression in primary keratinocytes [24], and HaCaT cells (the present study), addition of the xenobiotic menadione, which leads to continuous production of superoxide anions, caused a strong and long-lasting expression of HO-1 mRNA and protein. Since large amounts of superoxide anions are continuously generated by inflammatory cells [1] and other cell types [39] in wounded and psoriatic skin, these molecules are likely to be involved in the strong HO-1 expression seen in these tissues. Furthermore, nitric oxide, a potent stimulator of HO-1 expression in keratinocytes and other cell types [40,41], might play a role in HO-1 induction in inflamed skin, since this radical has been shown to be produced in wounded and psoriatic skin [42].…”
Section: Figure 7 Ho-1 Expression Is Upregulated By Hydrogen Peroxidementioning
confidence: 99%